Comparison between Milgram’s and Niven’s Obedience Theory on Nurses in Obedience using Personal Protective Equipment - Fauziah Rizki Andini; Thinni Nurul Rochmah; Linda Augustien Makalew; Maya Sari Dewi; Nabilah Bilqis (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Personal protective equipment (PPE) is a protection tool from potential hazards in the workplace. Low nurse obedience to using PPE at hospitals can increase the occurrence of work accidents. Nurse obedience to using PPE can be seen from the external factors suggested in Milgram's theory and internal factors explained in Niven's theory. This study aimed to compare nurse obedience to using PPE through the analyses of Milgram’s and Niven's theories. This study was an observational study with a cross-sectional study design. The population of this study was 187 nurses in the inpatient installation of Dr. R. Sosodoro Djatikoesoemo Bojonegoro Hospital. A sample of 113 nurses were then selected to be the respondents. The influence test was performed using linear regression. Based on Milgram's theory, external factors were more dominant in controlling obedience to using PPE. The external factors that had a significant effect included location status, proximity to authority figures, and the legitimacy of authority figures. Meanwhile, Niven's theory showed only one internal factor, understanding instruction, significantly influenced nurse obedience to use PPE. Therefore, it is recommended to formulate regulations and a more binding system through rewards and punishment to increase nurse obedience to using PPE. Abstrak: Alat Pelindung Diri (APD) merupakan alat yang melindungi diri dari potensi bahaya di tempat kerja. Rendahnya kepatuhan perawat dalam menggunakan APD di rumah sakit dapat meningkatkan terjadinya kecelakaan kerja. Kepatuhan perawat dalam menggunakan APD dapat dilihat dari faktor eksternal yang dikemukakan dalam teori Milgram dan faktor internal yang dijelaskan dalam teori Niven. Penelitian ini bertujuan untuk membandingkan kepatuhan perawat dalam menggunakan APD melalui analisis teori Milgram dan Niven. Penelitian ini merupakan penelitian observasional dengan desain penelitian cross sectional. Populasi penelitian ini adalah 187 perawat di Instalasi Rawat Inap RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro. Sampel sebanyak 113 perawat kemudian dipilih menjadi responden. Uji pengaruh dilakukan dengan menggunakan regresi linier. Berdasarkan teori Milgram, faktor eksternal lebih dominan dalam mengontrol kepatuhan penggunaan APD. Faktor eksternal yang berpengaruh signifikan antara lain status lokasi, kedekatan dengan figur otoritas, dan legitimasi figur otoritas. Sedangkan teori Niven hanya menunjukkan satu faktor internal yaitu pemahaman instruksi berpengaruh secara signifikan terhadap kepatuhan perawat dalam menggunakan APD. Oleh karena itu, direkomendasikan untuk merumuskan peraturan dan sistem yang lebih mengikat melalui reward and punishment untuk meningkatkan kepatuhan perawat dalam menggunakan APD.